PENINGKATAN MUTU PENDIDIKAN MELALUI OPTIMALISASI MANAJEMEN PERSONALIA - Ihin Solihin; Hisny Fajrussalam; Muhibbin Syah; Mohamad Erihadiana (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2020)
The purpose of this study is to find out about how to improve the quality of Islamic education through optimizing personnel management, and to find out what are the supporting and inhibiting factors for the implementation of personnel management in SMA Muhammadiyah 3 Plus Bandung City. The research that was carried out was included in qualitative descriptive research. The data collection method uses the method of observation, interviews, and documentation. Meanwhile, improving the quality of education is a systematic effort in school management to achieve progress from one stage to a higher level to produce added value according to applicable norms/standards. Management of improving the quality of Islamic education in schools is a quality improvement method that is based on school education itself, applies a set of techniques, is based on the availability of quantitative and qualitative data, and empowers all school components to continuously increase the capacity and capacity of school organizations to meet the needs of participants. students and society. By optimizing personnel management, it can continue to improve the quality of Islamic education. This is what the SMA Muhammadiyah 3 Plus Bandung City has done.Keywords:  Personnel Management, Quality of Education, Islam